Persistent Mathematical Gender Gap in Chilean National Assessment Simce [Brechas Persistentes de Género en Matemáticas en Las Pruebas Nacionales Chilenas simce1 - Matus-Correa, C (Universidad Austral de Chile, 2022)
This work quantifies and analyzes, from an emotional dimension viewpoint, persistent gender gaps in mathematics, for tenth grade, in Chilean high schools, according to Simce assessments. School Database with Male and Female average score recorded separately for 2016, 2017 and 2018, and gender gap average score were generated. These data was analyzed descriptively, and three-year persistent gap schools were identified. Correlation between female mathematic results and several indeces were determined, observing differential behavior between emotional dimension indices and mathematical outcomes among persistent-gap and non-persistent-gap schools. We concluded prevalent mathematical gender gaps in secondary schools spite off no gender differences at population level. We confirm emotional dimensional cognitive results relationship. © 2022. Estudios Pedagogicos. All Rights Reserved.